2014
DOI: 10.5897/ajar12.1841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicon on real time nitrogen management in a rice ecosystem

Abstract: Field experiments were conducted during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Prakash et al [34] reported increase in rice yield on additions of calcium silicate (CS) @ 3 -4 t ha -1 in coastal and hilly soils of Karnataka. Yogendra et al [35], Jawahar et al [36], Nagula et al [37], Malav et al [38] and Ali et al [39] opined that application of silicon alone produced the highest yield in rice. Foliar spray at different concentration increased the grain yield.…”
Section: Rice Yieldmentioning
confidence: 99%
“…Prakash et al [34] reported increase in rice yield on additions of calcium silicate (CS) @ 3 -4 t ha -1 in coastal and hilly soils of Karnataka. Yogendra et al [35], Jawahar et al [36], Nagula et al [37], Malav et al [38] and Ali et al [39] opined that application of silicon alone produced the highest yield in rice. Foliar spray at different concentration increased the grain yield.…”
Section: Rice Yieldmentioning
confidence: 99%
“…According to studies conducted to evaluate the use of silicon in agriculture, the rice crop shows increase in the number of leaves and in the number of spikelets per panicle, higher plant height and higher content and accumulation of silicon in plant shoots (Artigiani et al, 2012;Yogendra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%